PERAN KHALIFAH UMAR BIN KHATTAB DALAM MEMBANGUN PEMERINTAHAN ISLAM - Ira Septi Sulistiana; Achmad Maftuh Sujana; Illa Rohillah; Lilis Sulistiani; Anisa Fitriani (STID Raudlatul Iman Sumenep, 2025)
This study examines the role of Caliph Umar ibn al-Khattab in building the Islamic government through a historical approach and descriptive analysis of the strategic policies he implemented. The research highlights how Umar developed a systematic administrative structure by establishing the diwan, organizing territorial divisions, and appointing governors based on strict standards of integrity. It also explores Umar’s economic reforms, including tax management, the development of the baitul mal, and the regulation of conquered lands aimed at promoting public welfare. Furthermore, this study discusses his contributions to military organization, contextual legal reforms, and social policies that protected vulnerable groups within society. The findings indicate that Umar ibn al-Khattab successfully laid the foundation for a strong, stable, and sustainable Islamic government, providing a governance model that remains relevant for modern administrative systems.